Cycle camping in Victorian and Edwardian Ireland. Issue 3 (3rd July 2019) - Griffin, Brian
ABSTRACT: One of the most important aspects of cycling's impact on Ireland in the late Victorian and Edwardian periods is that it made recreational trips to the countryside easier for the urban middle class and better-off workers who could afford to buy bicycles. As this article shows, many Irish and other cyclists in this period combined their love of cycling and the countryside with camping trips. Cycle camping appealed to enthusiasts for a number of reasons, including its relative cheapness, the welcome temporary release that it brought from conventional urban modes of living, and the perceived mental and physical health benefits that it brought. A close examination of the activities and mindset of cycle campers in Ireland reveals that they had much in common with their contemporaries, the "muscular Christian" enthusiasts for sports.